FDI Outflows and Domestic Investment: Substitutes or Complements? Exploring the Indian Experience Nandita - Nandita Dasgupta (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
The recent phenomenon of rising outward foreign direct investment (OFDI) flows has raised serious policy concerns about its effects on the domestic investment and capital formation in the countries of origin of such FDI flows. Does OFDI stimulate domestic investment or does it crowd it out? The concern arises because OFDI activities could shift not only some of the production activities from home to foreign destinations but also could possibly threaten the availability of scarce financial resources at home by allocating resources abroad. All this have the potential to reduce domestic investment, thus lowering the long run sustainable economic growth and employment of the home economies. The central goal of this paper is to empirically explore the evidence of the macroeconomic relationship between OFDI and levels of domestic capital formation in India. Our study reveals that OFDI has long run strong positive causality with domestic investment and thus figures out to be a significant factor affecting domestic investment in India. It becomes imperative therefore that the nation make special effort to promote its OFDI through the designing of appropriate OFDI policies that would help stimulate its domestic investment now and in the future so as to sustain economic growth and development in the long run.
hdl:10398/9294
Keywords: 330; Domestic Investment; Structural Break; FDI Outflows; CMR Unit Root Test; ARDL Bounds Test; Multinationales Unternehmen; Auslandsinvestition; Indisch; Investition; Wirtschaftswachstum; Indien